2010
DOI: 10.1016/j.atmosenv.2010.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Improved land cover and emission factors for modeling biogenic volatile organic compounds emissions from Hong Kong

Abstract: a b s t r a c tThis paper describes a study of local biogenic volatile organic compounds (BVOC) emissions from the Hong Kong Special Administrative Region (HKSAR). An improved land cover and emission factor database was developed to estimate Hong Kong emissions using MEGAN, a BVOC emission model developed by Guenther et al. (2006). Field surveys of plant species composition and laboratory measurements of emission factors were combined with other data to improve existing land cover and emission factor data. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…That terpenoid emission estimate is similar to the 10.9 Tg estimated by Tie et al (2006). Since subtropical regions in China have severe ozone pollution and abundant forests, multiple studies have focused on local biogenic emissions and their potential effects on urban air quality Leung et al, 2010). As a typical city in northern China, Beijing faces severe ozone pollution in summer (Wang et al, 2006;Safieddine et al, 2016;Zhao et al, 2010).…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…That terpenoid emission estimate is similar to the 10.9 Tg estimated by Tie et al (2006). Since subtropical regions in China have severe ozone pollution and abundant forests, multiple studies have focused on local biogenic emissions and their potential effects on urban air quality Leung et al, 2010). As a typical city in northern China, Beijing faces severe ozone pollution in summer (Wang et al, 2006;Safieddine et al, 2016;Zhao et al, 2010).…”
Section: Introductionsupporting
confidence: 60%
“…The differences among the inputs do not have a significant effect on the temporal variability in the BVOC emissions estimated by the MEGAN model. Moreover, the ratio of BVOC emissions between the summer and winter seasons is 185-295, compared with a ratio of 9.77 in the Pearl River Delta region and 4.9 in Hong Kong (Leung et al, 2010). In temperate regions like Beijing, BVOC emissions display a very strong annual cycle, as there are almost no BVOC emissions in winter owing to the low winter biomass of temperate deciduous trees as well as low temperatures in winter.…”
Section: Quantity Of Bvoc Emissionsmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, in the present study the average isoprene emission flux in PRD was 0.35 Mg C km (2 in July, slightly higher than the summertime average of 0.31 Mg C km (2 reported by Wang et al (2011). Our total isoprene emission estimate in Hong Kong (0.35 Tg C) was also close to the given value of 0.39 Tg C by Tsui et al (2009), but both estimates were lower than the value reported by Leung et al (2010) (1.0 Tg C) by 60Á70%, due to the large differences in input data used (Table 3). Plotted against weather conditions, modelled biogenic emissions display a bell-shaped diurnal cycle, peaking at approximately 13:00 LST and nearly ceasing overnight (particularly for isoprene), with decreasing temperature and solar radiation (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 34%
“…In this study, PFT-specific emission factors of BVOCs for the four aggregated PFTs (i.e., broadleaf forest, coniferous forest, shrub, and cropland/grassland) were determined by local field observations in the literature Sakulyanontvittaya et al, 2008;Tsui et al, 2009;Leung et al, 2010;Wang et al, 2011). NO emission factors from soil were developed through measurements with static or dynamic chambers (Williams et al, 1992;Guenther et al, 2000).…”
Section: Megan Natural Emission Modelmentioning
confidence: 99%